The Use of Social Media in Designing The Writing Assessment for EFL Students - Rita Suswati; Syarbaini Saleh (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2019)
This research investigates social media as the assessment for EFL students at State University of Medan (UNIMED) of second semester English educational program. This research focuses on how social media influences the students’ competences in writing skills. The problems are how it influences their ability to develop their ideas in writing; develop the reading & writing materials; change the students’ opinion on social media in writing class. Questionnaire was designed to get the students’ thought on social media matter, their intention of social media for study, particularly in reading and writing topic and the influence of social media on their ability in developing the idea in writing class. The instruments used in this research were social media as Facebook, WhatsApp and Instagram as a text in reading & writing class. The population consisted of 80 students from two classes of English educational program. Data was analyzed using Research & Development Method (R&D) and the Linkert Scale to get the percentage of students’ perception. The findings of this paper indicate that students more enjoy and engage in writing class using social media as their assessments; using social media to develop ideas on a topic; and being more creative in writing skills. However, control and development are still needed on this topic.